Avaliação do Potencial Biotecnológico de Fungos Endofíticos de Piper hispidum - Oliveira, Rafael Lopes e (2010)
ABSTRACT - The species Piper hispidum (Piperaceae), known popularly as pepper-jack, occurs naturally in the Amazon and has high potential for economic development due to production of safrole, essential oil of proven insecticidal and antimicrobial activity with low toxicity. In order to minimize the extraction of some plant species (ex, P. hispidum), an interesting strategy is the use of endophytic microorganisms, since microorganisms associated with plants can produce compounds present in their hosts. Therefore, this study aimed to evaluate endophytic fungi isolated from P. hispidum and verify the biotechnological potential of the isolates, such as the antimicrobial activity, the ability to produce hydrolytic enzymes of commercial interest, the production of terpenes, antioxidant compounds and biocatalytic ability of two lipase producing isolates. Two specimens of P. hispidum from two spots of Manaus-AM were evaluated, where 58 fungal isolates were obtained. The isolates were distributed into nine morphological groups. Of these, 15 (25.9%) isolates produced compounds with antimicrobial activity against pathogenic bacteria, and 23 (39.2%) produced hydrolytic enzymes of industrial interest (amylase, cellulase, xylanase, lipase, pectinase and protease). The lipase producing fungi shown to be ineffective as biocatalyst mediating a esterification reaction. Within the crude extracts obtained from P. hispidum isolates evaluated in this study it was not detected the presence of safrole, citronellol; (R)- carvone and -pinene. The production of terpinolene and -cariofilene by two isolated could not be confirmed. The fungi crude extracts present lower antioxidant activity than ascorbic acid. In summary, it is important to note that the studies performed here showed that the investigation of the fungi diversity from tropical hosts clearly points out to new perspectives concerning the endophytic fungi potential. Keywords: Piperaceae, Endophytic Fungi, HPLC, Biological Activity.